Youth Protests in Lebanon: "All of Them Means All of Them" - El Amine, Adnan (International Higher Education, 2020)
On October 17, 2019, massive protests erupted in Lebanon, calling for the resignation of the country’s political leaders who had dominated its political life for three decades through patronage and corruption. The agenda of the protesters included demands for an independent government and a civil state. Youth constituted the main bulk of the protesters, with students at the core. The students engaged in the rallies, called for the support of the public university, and participated actively in daily discussion groups organized in public spaces.